2013
DOI: 10.1111/jan.12090
|View full text |Cite
|
Sign up to set email alerts
|

Nursing stress and patient care: real‐time investigation of the effect of nursing tasks and demands on psychological stress, physiological stress, and job performance: study protocol

Abstract: Data obtained in this study will be analysed to examine the relationships between nursing tasks, self-reported and physiological measures of stress and to assess the effect of occupational stress on multiple work outcomes. The results will inform theoretical understanding of nurse stress and its determinants and suggest possible targets for intervention to reduce stress and associated harmful consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 33 publications
1
36
0
4
Order By: Relevance
“…For these healthcare professionals, alternative measures able to detect processes either inaccessible to introspection or that the person might want to conceal may be necessary. Such measures include objective physiological manifestation of distress [48] or implicit measurement procedure [49] based on reaction time to assess automatic associations between regret and work.…”
Section: Discussionmentioning
confidence: 99%
“…For these healthcare professionals, alternative measures able to detect processes either inaccessible to introspection or that the person might want to conceal may be necessary. Such measures include objective physiological manifestation of distress [48] or implicit measurement procedure [49] based on reaction time to assess automatic associations between regret and work.…”
Section: Discussionmentioning
confidence: 99%
“…Stress as a phenomenon gained recogni tion in the nursing environment because of the data gleaned from patients and empirical studies that suggested that stress and health are closely linked (Burke, 2013;Farquharson et al, 2013). Nurses are seen to have more stress than most people due to the nature of the job and the system within which they work (Burke, 2013;Tuvesson, Eklund, & Wann-Hansson, 2012).…”
mentioning
confidence: 97%
“…Nurses are seen to have more stress than most people due to the nature of the job and the system within which they work (Burke, 2013;Tuvesson, Eklund, & Wann-Hansson, 2012). Studies of Burke (2013) and Farquharson et al (2013) indicated that nurses are often working through their break times (for instance lunch hours), working after hours or taking work home due to high work demands and insufficient numbers of staff. Burke (2013) also mentions the "culture of long hours" of the nursing profession, which -combined with inadequate rest breaks -lead to safety issues for both patients and nurses.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…[12] According to Laal, [13] stress has a multivariate effects on nurses' behavior including a proper and improper reactions resulting in different health problems, including: anxiety, deterioration in eating habits, sleep pattern disturbance, depression, and substance abuse. Farquharson et al, [14] added that Stress can affect the nurses' general health status, the quality of the services they provide, and their desire to remain in nursing.…”
Section: Introductionmentioning
confidence: 99%